Altered frontal electroencephalography as a potential correlate of acute dissociation in dissociative disorders: Novel findings from a mirror confrontation study - Schäflein, Eva; Mertens, Yoki Linn; Lejko, Nena; Beutler, Sarah; Sattel, Heribert; Sack, Martin (British Journal of Psychiatry Open, 2022)
People suffering from chronic dissociation often experience stress and detachment during self-perception. We tested 18 people with dissociative disorders not otherwise specified (DDNOS; compared with a matched sample of 18 healthy controls) undergoing a stress-inducing facial mirror confrontation paradigm, and measured acute dissociation and frontal electroencephalography (measured with a four-channel system) per experimental condition (e.g. confrontation with negative cognition). Linear mixed models indicated a significant group×time×condition effect, with DDNOS group depicting less electroencephalography power than healthy controls at the beginning of mirror confrontation combined with negative and positive cognition. This discrepancy-most prominent in the negative condition-diminished in the second minute. Correlational analyses depicted a positive association between initial electroencephalography power and acute dissociation in the DDNOS group. These preliminary findings may indicate altered neural processing in DDNOS, but require further investigation with more precise electroencephalography measures.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Dissociative disorders; electroencephalography; mirror; post-Traumatic stress disorder; self-perception

Exacerbation of central serous chorioretinopathy during trauma-confronting psychotherapy– a case report - Schäflein, Eva; Mardin, Christian; Morawa, Eva; Rudolf, Sophia; Erim, Yesim; Rhein, Cosima (BMC Psychiatry, 2024)
Background: Psychotherapy for post-traumatic stress disorder, in particular trauma-confronting psychotherapy, can be associated with increased stress. However, research on the somatic impact and psychosomatic interactions of these psychological stress reactions is lacking. We report on a 43-year old man whose central serous chorioretinopathy exacerbated upon trauma-confronting psychotherapy. Case presentation: We report on a man with pre-diagnosed, asymptomatic central serous chorioretinopathy who underwent inpatient psychosomatic therapy. He disclosed a history of sexual abuse by a family member and consequently showed intrusions, flashbacks, nightmares, avoidance behavior, and hyperarousal. Thus, we diagnosed post-traumatic stress disorder. After a stabilization phase, he underwent trauma-focused psychotherapy including trauma confrontation. In the course of this treatment, acute vision loss with blurred vision and image distortion of his right eye occurred. An ophthalmologic visit confirmed a relapse of a pre-diagnosed central serous chorioretinopathy. The analysis of stress biomarkers showed a decrease in testosterone levels and a noon peak in diurnal cortisol secretion, which is indicative of a stress reaction. Conclusion: Central serous chorioretinopathy may exacerbate upon psychotherapeutic treatment. In this case, an exacerbation of chorioretinopathy was observed in direct relation to the therapeutic intervention. Psychotherapists and ophthalmologists should collaborate in the psychotherapeutic treatment of patients with chorioretinopathy. Our case demonstrates the need to consider the possible increased stress levels during psychotherapy and resulting physical side effects, such as exacerbation of an existing condition. It is advisable to adjust the level of generated stress particularly well in the presence of stress-inducible physical diseases. Our case is a good example of the interplay between psychological and physical stress.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Case report; Central serous chorioretinopathy; Eye movement desensitization and reprocessing; Post-traumatic stress disorder; Trauma-focused psychotherapy

Long-term follow-up of a multimodal day clinic, group-based treatment program for patients with very high risk for complex posttraumatic stress disorder, and for patients with non-complex trauma-related disorders - Bever-Philipps, Anke; Silbermann, Andrea; Morawa, Eva; Schäflein, Eva; Stemmler, Mark; Erim, Yesim (Frontiers in Psychiatry, 2023)
Objective: The present study examined the follow-up of a multimodal day clinic group-based therapy program for patients with trauma-related disorders and investigated potential differences for patients with classic PTSD versus cPTSD. Method: Sixty-six patients were contacted 6 and 12 months after discharge of our 8-week program and completed various questionnaires (Essen Trauma Inventory (ETI), Beck Depression Inventory-Revised (BDI-II), Screening scale of complex PTSD (SkPTBS), Patient Health Questionnaire (PHQ)-Somatization, as well as single items to therapy utilization and life events in the interim period). Due to organizational reasons a control group could not be included. Statistical analyses included repeated-measures ANOVA with cPTSD as between-subject factor. Results: The reduction of depressive symptoms at discharge was persistent at 6 and 12 months follow-up. Somatization symptoms were increased at discharge, but were leveled out at 6 months follow-up. The same effect was found for cPTSD symptoms in those patients with non-complex trauma-related disorders: Their increase of cPTSD symptoms was flattened at 6 months follow-up. Patients with a very high risk for cPTSD showed a strong linear reduction of cPTSD symptoms from admission to discharge and 6 months follow-up. cPTSD patients had a higher symptom load compared to patients without cPTSD on all time points and scales. Conclusion: Multimodal, day clinic trauma-focused treatment is associated with positive changes even after 6 and 12 months. Positive therapy outcomes (reduced depression, reduced cPTSD symptoms for patients with a very high risk for cPTSD) could be maintained. However, PTSD symptomatology was not significantly reduced. Increases in somatoform symptoms were leveled out and can therefore be regarded as side effects of treatment, which may be connected with actualization of trauma in the intensive psychotherapeutic treatment. Further analyses should be applied in larger samples and a control group.
CRIS-Team Scopus Importer:2023-07-21
Keywords: CPTSD; day clinic; follow-up; group therapy; psychotherapy; PTSD; trauma

Paradoxical effect of anti-inflammatory drugs on IL-6 mRNA expression in patients with PTSD during treatment - Rhein, Cosima; Apelt, Isabella; Werner, Franziska; Schäflein, Eva; Adler, Werner; Reichel, Martin; Schug, Caterina; Morawa, Eva; Erim, Yesim (Journal of Neural Transmission, 2024)
The pathophysiology of posttraumatic stress disorder (PTSD) is associated with the activation of the innate immune system, including cytokines like interleukin 6 (IL-6). However, the role of IL-6 in the etiology and treatment of PTSD still remains elusive. We conducted a prospective controlled trial to investigate the development of IL-6 during psychosomatic treatment in individuals with PTSD in comparison with individuals without PTSD. We assessed IL-6 mRNA expression before and after 2 months of psychosomatic treatment in individuals with and without PTSD. Severities of PTSD and depressive symptoms were assessed in parallel. Linear mixed regression was applied for statistical analysis, including the factors diagnosis PTSD and pre–post treatment after subgrouping for intake of anti-inflammatory drugs. The development of IL-6 mRNA expression during treatment was affected by the use of anti-inflammatory drugs. In the subgroup without intake of anti-inflammatory drugs, no significant statistical treatment effect in individuals with and without PTSD emerged. In the subgroup of individuals taking anti-inflammatory drugs, a significant interaction effect of the factors pre–post treatment and diagnosis PTSD was observed. Whereas IL-6 mRNA expression in individuals without PTSD decreased according to amelioration of symptoms, IL-6 mRNA expression in individuals with PTSD increased significantly during treatment, in opposite direction to symptom severity. Anti-inflammatory drugs might affect IL-6 mRNA expression in individuals with PTSD in a paradoxical way. This study offers a further piece of evidence that IL-6 could be involved in the pathophysiology of PTSD and PTSD-specific immunologic molecular mechanisms.
CRIS-Team Scopus Importer:2024-05-03
Keywords: Anti-inflammatory drugs; Interleukin 6; Posttraumatic stress disorder; Psychotherapy; Therapy outcome